Chronic osteomyelitis of the tibia in a runner: catastrophic consequences of shin splints. (1st March 2018) - Hammad, Yunes Nadim; Johnson, Abigail; Norrish, Alan
Abstract : Medial tibial stress syndrome and chronic osteomyelitis are conditions that are traditionally thought to affect very different patient groups. We present a case of shin splints in a recreational long-distance runner, complicated by chronic osteomyelitis of the tibia. This is a unique case in which the microtrauma resulting from shin splints was implicated as an entry point for bacterial infection into the bone. Clinical evaluation and bone biopsy culture results indicated haematogenous spread of bacteria originating from the oral cavity. The patient required surgical resection of the affected bone and a prolonged course of intravenous antibiotic treatment. We illustrate that when shin splints show signs of acute inflammation with delayed recovery, the possibility of osteomyelitis should be kept in mind.